2017
DOI: 10.1007/s00428-017-2115-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum HE4 is correlated to prognostic factors and survival in patients with endometrial cancer

Abstract: The extent of surgery and the decision for adjuvant treatment in patients with endometrial cancer (EC) depend on the presence of risk factors for lymph node metastases and disease recurrence. Postoperative markers such as myometrial infiltration and specific mutations can select patients for adjuvant treatment but will not influence surgical planning. A biomarker stratifying patients into low-risk and high-risk groups before surgery could identify patients who benefit from more extensive surgery. Therefore, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 36 publications
11
33
1
Order By: Relevance
“…Current study results are close to Alonso et al [25] who found that Annexin II can be used as a potential marker of endometrial carcinoma recurrence, through the promotion of endometrial carcinoma metastasis and in line with the recent studies by Stiekema et al [26] who observed that HE-4 was an independent prognostic factor for both DFS and OS in patients with EC.…”
Section: Discussionsupporting
confidence: 91%
“…Current study results are close to Alonso et al [25] who found that Annexin II can be used as a potential marker of endometrial carcinoma recurrence, through the promotion of endometrial carcinoma metastasis and in line with the recent studies by Stiekema et al [26] who observed that HE-4 was an independent prognostic factor for both DFS and OS in patients with EC.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, MKI67 and PTEN were also validated in tissue samples from imprint smears [51][52][53], as well as CDH1, which was analyzed in uterine aspirates using mass spectrometry-based approaches [54]. MUC16 and WFDC2 have been extensively studied in serum samples by antibody-based techniques such as ELISA or chemiluminescence techniques [50,[55][56][57] and L1CAM was also validated in serum but just in one study [58].…”
Section: Prognostic Protein Biomarkers In Ecmentioning
confidence: 99%
“…However, the number of studies on the exploration of biomarkers that could help early diagnosis and predict the prognosis of patients with EC is still limited. Although there have been several studies in EC patients examining serum indices, such as cancer antigen 125 (CA125), human epididymis protein (HE4), and VEGF (25,(31)(32)(33), their reliability and repeatability still lack consensus.…”
Section: Discussionmentioning
confidence: 99%